2020
DOI: 10.1111/jan.14339
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of pre‐operative patient readiness on surgical outcomes: A structural equation model analysis

Abstract: Aims:To determine the mediating role of surgical readiness on patient characteristics (surgical risk, type of surgery, pre-operative anxiety, and health literacy) and its influence on surgical outcomes (pain, postoperative complications, and surgical experience).Design: Correlational, theory testing using structural equation modelling. Methods:A total of 376 consecutively selected surgical patients from four tertiary hospitals were recruited and followed-up 48-72 hr postoperatively from May-October 2017. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…After completing this review, we identified an opportunity for perioperative nurses to provide holistic preoperative care that is not limited to physical preparation, but includes mental and psychosocial dimensions. The nurses should consider promoting educational programs for preoperative readiness to improve the patient’s physical and psychological outcomes (eg, decreased anxiety, improved pain management), resulting in a positive surgical experience for the patient 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After completing this review, we identified an opportunity for perioperative nurses to provide holistic preoperative care that is not limited to physical preparation, but includes mental and psychosocial dimensions. The nurses should consider promoting educational programs for preoperative readiness to improve the patient’s physical and psychological outcomes (eg, decreased anxiety, improved pain management), resulting in a positive surgical experience for the patient 9 …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, patient preparation focuses on implementing a preoperative bundle that includes medication administration, 5 laboratory assessments, 5 and health teaching 6 . Some experts separate readiness from preparedness, recognizing the need for physical preparation 7,8 and the importance of the mental and emotional state of a patient preparing for surgery 7,9 . Perioperative nurses promote surgical readiness through the delivery of preoperative education that can increase the patient’s knowledge and satisfaction and, in some cases, reduce anxiety in patients preparing for surgery 10 .…”
mentioning
confidence: 99%
“…The sample size was calculated through GPower version 3.1.9 as follows: validity of sample size was 95.1%, effect size was 0.3, and significance level was 5% (bilateral) in 134 respondents. In order to ensure the statistical stability of the structural equation model, the sample size was expanded to >200 cases (16). This study adhered to the Helsinki declaration (as revised in 2013), principles of informed consent, security protection, privacy and confidentiality, and fairness and transparency.…”
Section: Methodsmentioning
confidence: 99%
“…The total score of BFS was 80 [51-90], and the 5 dimensions were: acceptance, 11 [7][8][9][10][11][12][13]; family relationship, 21 [14][15][16][17][18][19][20][21][22][23][24]; personal growth, 27 [19][20][21][22][23][24][25][26][27][28][29][30][31]; social relationship, 10 [7][8][9][10][11][12]; and health behavior, 9 [7][8][9][10][11][12], respectively. The total score of CBI was 34 [23][24][25][26][27][28][29][30]…”
Section: The Scores Of Bfs Cbi and Hadsmentioning
confidence: 99%
See 1 more Smart Citation